Analysis of Factors Associated with The Incidence of HIV AIDS among Housewives: A Mixed-Methods Study - Windiramadhan, Alvian Pristy; Carsita, Wenny Nugrahati; Husnaniyah, Dedeh (Babali Nursing Research, 2026)
Introduction: While new HIV infections among key populations have declined, infections among women traditionally considered low-risk, particularly housewives, have increased. The problem that arises in housewives with HIV is the tendency to keep their disease status secret, resulting in delayed diagnosis and treatment, which leads to an increase in HIV transmission. However, factors related to HIV incidence in housewives have not been sufficiently explored. This study aims to analyze factors associated with HIV/AIDS incidence among housewives.Methods: This study used a sequential explanatory mixed methods design. A total of 323 respondents were involved in the quantitative study, while the qualitative study involved 6 housewives and 4 triangulation informants, including family members, nurses, counselors, and non-governmental organization leaders. The sampling technique used was purposive, based on the inclusion criteria. This study was conducted at a hospital in Indramayu Regency. Data analysis used the Structural Equation Modeling-Partial Least Squares (SEM-PLS).Results: Structural model analysis showed that predisposing factors and sexual behavior have a significant direct effect on HIV incidence, while precipitating factors have an indirect effect through sexual behavior.Conclusion: HIV incidence among housewives is influenced by predisposing factors, precipitating factors, and risky sexual behavior. HIV incidence among housewives is not only influenced by individual behavior, but also by social, economic, cultural, and gender relations within the household. Therefore, HIV prevention must be carried out comprehensively, taking these aspects into account.